PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI RSUD LANTO DAENG PASEWANG KABUPATEN JENEPONTO - Mukhtar Tompo; Muhlis Madani; Fatmawati Fatmawati (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2021)
The purpose of this study is to describe and analyze the application of the principles of good governance in public services, the supporting and inhibiting factors for the application of the principles of good governance, and the output of public services at the Lanto daeng Pasewang Regional General Hospital, Jeneponto Regency. This research uses qualitative research. The instrument used in this study was the interview with the informant, then the answers from the informants were analyzed and described descriptively. The results show that the implementation of good governance related to participation has been carried out, but there is still something that needs to be invited to participate, namely community participation (NGO), related to transparency has not been fully implemented, related to responsiveness has not been implemented, related to accountability is not applied by the management of Lanto Daeng Pasewang Regional Hospital. . Supporting factors in the process of implementing the principles of good governance are the factors of cooperation and communication factors. The output of the service system at Lanto Daeng Pasewang Regional Hospital has not been effective in implementing the service standards of the RSUD considering that the administration is still slow and is still waiting for days to get the results of the examination.